CABI's agricultural library and documentation service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A unique, compre hensive range of specialist documentation services is provided by CAB International's Library Service (CLS), which is based near Ascot, UK. The library contains one of the largest collections of agricultural science literature....